2021
DOI: 10.1002/oby.23282
|View full text |Cite
|
Sign up to set email alerts
|

Omega‐6 and omega‐3 oxylipins as potential markers of cardiometabolic risk in young adults

Abstract: Objective Omega‐6 and omega‐3 oxylipins are known to play a role in inflammation and cardiometabolic diseases in preclinical models. The associations between plasma levels of omega‐6 and omega‐3 polyunsaturated fatty acid–derived oxylipins and body composition and cardiometabolic risk factors in young adults were assessed. Methods Body composition, brown adipose tissue, traditional serum cardiometabolic risk factors, inflammatory markers, and a panel of 83 oxylipins were analyzed in 133 young adults (age 22.1[… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 47 publications
(92 reference statements)
3
16
1
Order By: Relevance
“…Consumption of inulin also tended to decrease the amount of HETEs produced by LOX. In line with our findings, amounts of 15-HETrE, 5-HETE, 12-HETE and 15-HETE in plasma are increased in obesity conditions in humans [ 72 , 73 ]. PGE 2 derived from arachidonic acid via COX enzyme was the only selected and detected eicosanoid that tended to increase after receiving inulin.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consumption of inulin also tended to decrease the amount of HETEs produced by LOX. In line with our findings, amounts of 15-HETrE, 5-HETE, 12-HETE and 15-HETE in plasma are increased in obesity conditions in humans [ 72 , 73 ]. PGE 2 derived from arachidonic acid via COX enzyme was the only selected and detected eicosanoid that tended to increase after receiving inulin.…”
Section: Discussionsupporting
confidence: 91%
“…Although PGE 2 is considered a pro-inflammatory lipid mediator, it can exhibit anti-inflammatory properties by reducing the production of cytokine tumor necrosis factor α, inhibiting 5-LOX enzyme involved in producing pro-inflammatory 4-series leukotrienes and 5-HETE, and enhancing 15-LOX enzyme involved in producing pro-resolving lipoxin A 4 [ 10 ]. In fact, plasma PGE 2 may be negatively correlated with parameters of adiposity, insulin resistance, and fatty liver in healthy young adults [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…High omega-6 oxylipins and eCBs are indicators of higher pro-inflammatory status, high adiposity levels, cardiovascular disruption, liver dysfunction, and/or oxidative stress, 5 , 7 , 9 , 10 , 12 , 46 , 48 , 49 which concur with the findings observed in our cohort of young, sedentary adults. 50 Interestingly, we found that long-term exercise training, was an effective therapy to decrease the plasma levels of these metabolites. Acute exercise has been demonstrated to induce higher analgesic effects through increased eCBs levels.…”
Section: Discussionmentioning
confidence: 88%
“…All blood samples were immediately centrifuged to obtain plasma aliquots (obtained with Vacutainer ® Hemogard™ tubes, containing the potassium salt of ethylenediaminetetraacetic acid as an anticoagulant) and stored at −80 °C. Plasma levels of omega-3 and omega-6 oxylipins were measured with a targeted metabolomics approach using liquid chromatography-tandem mass spectrometry (LC-MS/MS), with a method validated according to the Food and Drug Administration (FDA) bioanalytical method validation guidelines [ 25 ].…”
Section: Methodsmentioning
confidence: 99%